Communication Strategy of the North Sumatra Regional Office of the Ministry of Religious Affairs in Socializing Religious Moderation in the State Islamic High School Environment of Medan City - Soraya, Ade; Mailin, Mailin; Nasution, Syawaluddin (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This research aims to analyze the organizational communication of the Regional Office of the Ministry of Religion of North Sumatra in promoting religious moderation in the Madrasah environment. The research method used is qualitative. The research location is the Regional Office of the Ministry of Religion, North Sumatra. Determining the subjects in this research was carried out using purposive sampling, where the subjects or sources of information were those who were related and were deemed worthy as research subjects and were also very knowledgeable about the information. The research results show that the development of religious moderation activities in the field has reached a positive stage. The Ministry of Religion team has succeeded in socializing the concept of religious moderation in madrasas, and the response from the madrasah. The madrasah has welcomed the presence of the Ministry of Religion team which plays a role in conveying information related to religious moderation. This positive response shows that organizational communication between the Ministry of Religion and madrasas is effective. The outreach activities carried out by the Ministry of Religion team can be considered a positive step in increasing understanding and awareness among madrasahs regarding religious moderation.